Prescribed anti‐glaucoma medication consumption and road traffic crash. Issue 5 (16th December 2022) - Lu, Li; Contrand, Benjamin; Schweitzer, Cedric; Gadegbeku, Blandine; Delcourt, Cécile; Lagarde, Emmanuel
Abstract: Background: Glaucoma is one of the leading causes of visual impairment worldwide. Influence of visual defects associated with this condition, as well as potential side effects of anti‐glaucoma medications on driving may be a relevant traffic safety concern. This study therefore aimed to investigate whether and/or to what extent prescribed anti‐glaucoma medicine consumption is associated with increased likelihood of crash risk, and traffic crash responsibility among drivers involved in road traffic crashes. Methods: Data from three French national databases were extracted and matched as part of the CESIR (a combination of studies on health and road safety) project. The sample included 201 497 drivers involved in an injurious road crash in France from July 1, 2005 to December 31, 2015, and an age‐ and sex‐matched control group (113 357 drivers) that was randomly drawn from the general population. Exposure to anti‐glaucoma medications were compared between responsible and non‐responsible drivers involved in a crash and between drivers involved in a crash and people from the control group. Results: The proportion of drivers with prescribed anti‐glaucoma medicine markedly increased with age. One type (OR = 0.79, 95% CI: 0.72–0.86) and two or more types (OR = 0.82, 95% CI: 0.68–0.98) anti‐glaucoma medicine prescriptions were less frequent in crash‐involved drivers than in controls. One type (OR = 0.99, 95% CI: 0.88–1.12) and two or more types (OR = 1.04, 95% CI: 0.82–1.33) anti‐glaucoma medicine prescriptions were not associated with crash responsibility. Conclusion: Our findings are reassuring as regard to existing guidelines for safe driving for individuals using anti‐glaucoma medications. Our results also suggest that driving behavior adaptation is effective mitigating potential traffic crash risks for people diagnosed with glaucoma.